Descriptive Epidemiology of Somatising Tendency :Findings from the CUPID Study - (:unkn) unknown (My University, 2016)
Somatisingtendency,definedasapredispositiontoworry aboutcommonsomaticsymptoms,isimportantly associatedwithvariousaspectsofhealthandhealth-relatedbehaviour, includingmusculoskeletalpainandassociateddisability.Toexploreitsepidemiological characteristics,andhowitcanbespecifiedmostefficiently,weanalyseddatafromaninternationallongitudinalstudy.Abaselinequestionnaire,whichincludedquestionsfrom the BriefSymptomInventoryaboutsevencommonsymptoms,wascompletedby12,072participantsaged20–59from 46occupationalgroupsin18countries(responserate70%).The sevensymptomswereallmutually associated(oddsratiosforpairwiseassociations3.4to 9.3),andeachcontributedtoameasureofsomatisingtendencythatexhibitedanexposureresponserelationshipbothwithmulti-sitepain(prevalencerateratiosuptosix),andalso withsicknessabsencefornon-musculoskeletalreasons.Inmostparticipants,thelevelof somatisingtendencywaslittlechangedwhenreassessedafter ameanintervalof14 months(75%havingachangeof0or1intheirsymptomcount),althoughthespecificsymptomsreportedatfollow-upoftendifferedfromthoseatbaseline.Somatisingtendencywas morecommoninwomenthanmen,especiallyatolderages,andvariedmarkedlyacross the46occupationalgroupsstudied,withhigherratesinSouthandCentralAmerica.Itwas weaklyassociatedwithsmoking,butnotwithlevelofeducation.Ourstudysupportstheuse ofquestionsfromtheBriefSymptomInventoryasamethodformeasuringsomatisingtendency,andsuggeststhatinadultsofworkingage,itisafairly stabletrait.
Keywords: Descriptive epidemiology; Somatising